Pleistocene hunter-gatherer coastal adaptations in Atlantic Iberia - Bicho, Nuno; Esteves, Eduardo (Frontiers in Earth Science, 2022)
Coastal prehistoric hunter-gatherers in Atlantic Iberia were particularly important to understanding Paleolithic human innovation and resilience. This study will focus on Middle and Upper Paleolithic adaptations to the Iberian Atlantic border. Elements such as intensity and diversity of marine foods, site location, distance to shore, submerged platform, and bathymetry are discussed for the region between Gibraltar and the Gulf of Biscay.